The Small Business Role In Socio-Economic Development In The Digital Economy Development - Rakhmonovna, Makhmudova Dilbar (The journal of contemporary issues in business and government, 2021)
The article discusses “The small business role in socio-economic development in the digital economy development”, identifies our country role in the international rating index, and provides a detailed definition of the current smart management and digital economy. It also shows the importance of digital technologies in the transition to an innovative economy and the gradual evolutionary development stages, the digital economy characteristics and its introduction directions. In our country transition to a new level, reasonable proposals and recommendations have been made on the issues of achieving socio-economic development through the small business management improvement.